DIETARY ASSESSMENT OF MARWARI COMMUNITY OF JORHAT, INDIA - Borkotoky, Priyakshi; Bhattacharyya, Ruma (International Journal of Research -GRANTHAALAYAH, 2022)
Nutritionally animal proteins are better for its superior bioavailibity, however due to the presence of high saturated fat content in food of animal origin, vegetarian diets are widely considered as healthy. But due to lack of proper information the nutritional adequacy of vegetarian diet followed by different communities is still uncertain. The Marwari is a strict ethnic vegetarian community of Indian, originated from Rajasthan, India. Due to business purpose a fraction of the Marwari community migrated to and residing at Jorhat, India. In view of lack of information on nutritional status of this particular community, a study was conducted to determine their nutrient intakes and variability in diets and dietary risk factors; weighing against similar values among Marwaries residing in Rajasthan. Total 200 samples were randomly selected and information on demographic profile, anthropometry, dietary habit and health status of the sample population were collected with the help of an interview schedule and a pre tested food frequency questionnaire. Findings were presented as percentage or mean with standard error. The food culture of the Assamese Marwari community is established within the traditional Marwari diet frame with strict vegetarianism and high fat diet, mostly contributed by clarified butter or desi ghee. However, the diet of the sample population was influenced by dissimilarity in agro climatic condition between Rajasthan and Assam. This study evaluates the dietary pattern, influence of environmental factor on traditional diet pattern due to migration and prevalence of risk factors of coronary heart and/or other non-communicable diseases among the sample population.